(3aVGFd ef GSeI CMeO heMeOs - (3GHf HcjQ , GdMSjf Hf CMeO Hf YHO Gddg GdUjQaj GdMGaX, CHh YHO Gddg,J (B388 (3g` s
(3ChdgG (B:s
(3CfHCfG GdCNhGf CHh ehSi YHO Gddg hGHh GdaQL YHO GdQMef Yf CHj CeGeI GdHGgdi bGd (B: (3bGd QShd Gddg Udi Gddg Ydjg hSde (B: (3ef hdO ehdhO aSeGg eMeOkG JHQcG Hg cGf gh hehdhOg ai GdLfI s
(3BNQgG (B:s
(3bGd QShd Gddg Udi Gddg Ydjg hSde (B: (3gOjI ecGaCI , hgOjI dFdG jbGd dQLGd ShA , hgOjI jKjHg Gddg JYGdi s
(3Vef eLehY , JQJjHgG (B: (3ef U (B227 - (3U(B229s
(3WHYJ gPg GdQSGdI aj GdgfO Sf`(B1961(3``I e Yf eNWhWI djOf (B,(3hgj JNJda Yf eNWhWJfG gPgs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B231s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B311 s
Keywords: (3GdJGQjNs